Traditional Warung Strategy In The Face Of Business Competition With Modern Stores (Study In Medan Helvetia District) - Ainun, Ainun Mardhiyah (Journal Of Management Analytical and Solution (JoMAS), 2022)
Modern retail activities in Indonesia are currently experiencing development, have entered residential areas close to the community. The type of retail trade is divided into two, namely modern retail represented by supermarkets, hypermart and minimarkets such as alfamart, indomaret and others, while traditional retail is directly represented by traditional stalls located in traditional markets and settlements. This research was conducted in Medan Helvetia Subdistrict of Medan City of North Sumatra. This research was conducted to traditional stall business owners in the hopes of knowing what factors can affect business competition between traditional stalls and modern stores and also know what impact occurs in business competition between traditional stalls and modern stores and know the strategy of traditional stall owners in undergoing business competition with modern stores. Medan Helvetia Subdistrict area is used as a research location because Helvetia District is one of the Districts in Medan City that some residents have the livelihood of retail business (in this case traditional stalls). After conducting research on what factors can affect business competition between traditional stalls and modern stores and also know what impact occurs in business competition between traditional stalls and modern stores and know the strategy of traditional stall owners in undergoing business competition with modern stores on traditional stall owners in Medan Helvetia District,Â  Then the researcher will get information about what factors can affect business competition between traditional stalls and modern stores and also know what impact occurs in business competition between traditional stalls and modern stores and know the strategy of traditional stall owners. To achieve these goals, the methods or approaches used in this study are descriptive with qualitative approaches. The results obtained are concerned that the factors that affect business competition between traditional stalls and modern stores are prices, location, service and product completeness. The existence of modern stores is not so influential on traditional stalls because they pay attention to competing strategies, namely by paying attention to prices, location, service and product completeness